How to think like Socrates : ancient philosophy as a way of life in the modern world - Robertson, Donald, 1972- (St. Martin's Press, an imprint of St. Martin's Publishing Group, 2024)
"How can we apply the teachings of the greatest ancient philosopher to modern life? Socrates is the quintessential Athenian philosopher, the source of the entire Western philosophical tradition, and Godfather to the Stoics. He spent his life teaching practical philosophy to ordinary people in the streets of Athens, yet few people today are familiar with the wisdom he has to offer us. How to Think Like Socrates is an accessible and informative guide to the life of one of the greatest thinkers in history, and the first book to focus on applying his ideas to our daily lives. Author Donald J. Robertson transports readers back to ancient Athens, expertly weaving together a page-turning account of a philosopher who eschewed material pleasures and stood by his beliefs, even in the face of controversy, with a steadfastness that ultimately resulted in his execution. How to Think Like Socrates highlights the continuing value of the Socratic Method to modern life. As a practicing cognitive-behavioral psychotherapist, Robertson also uses his expertise to reveal many parallels between the evidence-based concepts and techniques of modern psychology and the philosophy of Socrates, and shows how his philosophical insights can guide and benefit all of us to this day"--